(untitled) (Journal of the College of Basic Education, 2022)
The present study aims to the obstacles of Taekwondo from the point view of the players in Baghdad The study sample consisted of(100) players,(85) males and (15) females, distributed on (7) clubs in Baghdad. To achieve the objective of the study , the researcher designed a questionnaire consisting of (52) items distributed on four areas, obstacles related to the training programs in the clubs, (14) items, obstacles related to the financial resources, (12) items , obstacles related to the training method, (13) items, and obstacles related to the instructor ,(13) items , after distributing and re-gathering the questionnaires on the members of the study sample and after conducting the necessary statistical treatments, the results of data analysis indicated important of which are. The presence of obstacles associated with Taekwondo from the point view of the players with a medium degree. The presence of statistically significant differences at the level (0,05) in the views of the study members regarding the obstacles related to the fields of (training programs in the clubs financial resources the training method , and obstacles of Taekwondo) due to the variable of sex for the benefit of females. The presence of statistically significant differences at the significance level (0,05) in the views of the study members regarding the obstacles related to the fields (training programs in the clubs and centers, the training method obstacles of Taekwondo) duo to the variable of number of years of exercise for the benefit of the number of years of exercise (5-10 years), (more than 10 years)The absence of statistically significant differences at the significant level (0,05) in the views of the study members regarding the obstacles related to the financial resources and the trainer according to the variable of the number of years of exercise.